Regional management features tourism in Ukraine - Zaitseva, Marina (The Journal of V. N. Karazin Kharkiv National University. Series: International Relations. Economics. Country Studies. Tourism, 1970)
Within the economy of different regions of Ukraine under modern conditions, tourism  plays an increasingly important role. However, not all regions are able to provide long-term sustainable development of tourism on its territory. One of the main causes of problems in the development of regional tourism is the imperfection of the regional system of tourism management. This article discusses key issues concerning the impact of tourism on the regional economy and proposes a number of measures to reform the management of tourism activities at the regional level.